Faktor Struktural Social Appearance Anxiety Scale - Wardani, Asti Kusuma; Hidayah, Nurul; Safaria, Triantoro (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2023)
Abstract This study aimed to adopt social appearance anxiety scale developed by Hart (2008). This study showed the instrument fit for Indonesian adolenscent. Analysis used to show structure factor of social appearance anxiety. Research respondent were 100 adolenscent in Yogyakarta. The result showed p-value = 0,63 ( >0,5). While from RMSEA and TLI showed fit model. keywords: social appearance anxiety, structure factor